2015
DOI: 10.5194/isprsarchives-xl-5-w4-461-2015
|View full text |Cite
|
Sign up to set email alerts
|

Aerial Mapping and Multi-Sensors Approaches From Remote Sensing Applied to the Roman Archaeological Heritage

Abstract: ABSTRACT:This report details the preliminary results of the research focused on Roman archaeological heritage in the Middle Ebro Valley (Spain). The principal objective of this project was to obtain several different readings by means of a UAV equipped with different sensors. Firstly, it has been possible to obtain accurate maps, 3D models and digital elevation models of the site. Secondly, it has been possible to investigate and define archaeological remains still underground, via a new methodology which util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…False-color multichannel composites were produced either by using the MS datasets for image-based modeling directly or by combining overlapping orthoimages of different wavelengths. Most MS composites where either reduced through PCA [50,84,109] or processed for normalized difference vegetation index (NDVI) mapping [50,52,54,56,57,60,[66][67][68][70][71][72]75,76,[84][85][86]97,99,104,109], in order to enhance the contrast between the proxies of buried remains and the landscape matrix. It is worth mentioning that a few studies [50,60,75,86,97,99] reported the use of multiple radiometric vegetation and soil indices to identify which wavelength combinations maximized the local contrasts.…”
Section: State-of-the-artmentioning
confidence: 99%
“…False-color multichannel composites were produced either by using the MS datasets for image-based modeling directly or by combining overlapping orthoimages of different wavelengths. Most MS composites where either reduced through PCA [50,84,109] or processed for normalized difference vegetation index (NDVI) mapping [50,52,54,56,57,60,[66][67][68][70][71][72]75,76,[84][85][86]97,99,104,109], in order to enhance the contrast between the proxies of buried remains and the landscape matrix. It is worth mentioning that a few studies [50,60,75,86,97,99] reported the use of multiple radiometric vegetation and soil indices to identify which wavelength combinations maximized the local contrasts.…”
Section: State-of-the-artmentioning
confidence: 99%
“…The combination of affordable and easy to use software with affordable and easy to use autonomous AUVs as platforms, provided an excellent mapping tool for an increased number of users and applications; mapping applications, mainly orthophoto creation [4], DEM extraction, archaeology [13], coastal mapping [14], city mapping, monument 3D modelling [15], remote sensing, precision agriculture, security monitoring, infrastructure recording, etc.…”
Section: Previous Workmentioning
confidence: 99%
“…The latest allowing checking the site not only from above the surface but also at the height of the monument and at close range. For their intrinsic characteristics of ease of use, affordability, availability and the ability to change the payload, recently, archaeologists have shown a great interest in UAVs as highlighted by recent publications [4][5][6][7][8][9][10][11][12] where Fixed-wing [13] and multi-rotor drones [14,15] have become the most used UAV platforms.…”
Section: Introductionmentioning
confidence: 99%